PALINOLOGIA DE LA FORMACION AGUA COLORADA (CARBONIFERO SUPERIOR), SIERRA DE FAMATINA, PROVINCIA DE LA RIOJA, ARGENTINA. I. GRANOS DE POLEN (Ameghiniana, 2013)
PALYNOLOGY OF THE AGUA COLORADA FORMATION (CARBONIFEROUS), FAMATINA RANGE, LA RIOJA PROVINCE. ARGENTINA. I. POLLEN GRAINS.The first part of a comprehensive taxonomic survey of the carboniferous palynological assemblage from the Agua Colorada Formation is presented. Samples for this study have been obtained from localities of the South-Southwest flank of Famatina Range, La Rioja Province: Los Berros-Blanco, Casa Blanca, Casa de Lata, Agua Colorada, Puesto El Vallecito, Puesto Primera Agua, Las Gredas and Las Trancas creeks and Santa Rosa mine. The following saccate pollen species are here described: Plicatipollenites malabarensis (Potonié & Sah) Foster, Pl. gondwanensis (Balme & Hennelly) Lele, Pl. trigonalis Lele, Potonieisporites barrelis Tiwari, P. brasiliensis (Nahuys, Alpem & Ybert) Archangelsky & Gamerro, P. congoensis Bose & Maheshwari, P. densus Maheshwari, P. lelei Maheshwari, P. magnus Lele & Karim, P. methoris (Hart) Foster, P. neglectus Potonié & Sah, P. novicus Bharadwaj, P. triangulatus Tiwari, Cannanoropotlis densus (Lele) Bose & Maheshwari, C. janakii Potonié & Sah, C. mehtae (Lele) Bose & Maheshwari, C. sp. cf. C. triangularis (Mehta) Bose & Maheshwari, Parasaccites densus Maheshwari, P. sp. A. Caheniasaccites densus Lele & Karim emend., C. ovatus Bose & Kar emend., C. verrucosus (González Amicón) nov. comb., Circumplicatipotlenites plicatus Ottone & Azcuy, Crucisaccites latisulcatus Lele & Maithy, C. monoletus Maithy, Gondwanapollis frenguellii (Césari) nov. comb., G. ganjraensis Lele & Maithy, G. lenticulatus nov. sp., Colpisaccites granulosus Archangelsky & Gamerro, Alisporites sp. A, Pteruchipollenites gracilis (Segroves) Foster, Platysaccus sp. A, P. sp. B, Limitisporites hexagonalis Bose & Maheshwari, L. rectus Leschik, L. sp. A, Protohaploxypinus sp. cf. P. amplus (Balrne & Hennelly) Hart, P. sp. A and P. sp. B. Some taxa are recorded for the first time in the Argentine Carboniferous. Criteria used for a consistent parataxonomic system of monosaccate pollen grains classification are discussed, particularly those regarding the genera Plicatipollenites Lele, Potonieisporites Bharadwaj emend. Bharadwaj, Cannanoropollis Potonié & Sah, Parasaccites Bharadwaj & Tiwari and Caheniasaccites Bose & Kar emend. Archangelsky & Gamerro. The specific assignation of Argentine material to the genus Florinites Schopf, Wilson & Benttal emend. Millay & Taylor, are here discussed. The botanical affinity, chronological range and regional and worldwide distribution of the palynomorphs, are reported.